Clinical anatomy of temporo-mandibular joint muscles (Эндодонтия Today)
Use of classical morphometric methods in combination with contemporary (X-ray radiometric analysis), allows to do study in more detail clinical aspects of functional features of a temporo-mandibular joint. The regularities in muscle structures of a joint presented in this work can be added in earlier researches and do communication with clinic more organic and indissoluble.